Scientific support for elite junior japanese tennis players - example of biomechanical data feedback in tennis serve - Michikami, S.; Umebayashi, K.; Sato, Y.; Suda, K. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Teaching tennis is both an art and a science. This will imply that sports science is useful for improvement of tennis performance and stroke techniques. In recent years, a powerful and accurate tennis serve is one of the important factors in winning modern tennis matches, and biomechanical analyses on the serving motion have been done by several researchers. However, little scientific support based on the biomechanical data in the serving motion has been done. The purpose of this study was to investigate the two serving motions, good serve (the fastest serve hit into target area) and poor serve (fault serve), in elite junior Japanese tennis players, and to obtain suggestions for the improvement in the serving technique of each player. In addition, we tried to provide the data and the knowledge obtained for coaches and players as soon as possible. Methods The subjects were 18 male and 19 female elite junior players (age: 12-17 yrs.), and one female professional tennis player (age: 24 yrs.). Players were told to serve five times in succession assuming playing at tennis matches. Serving motion of the players was videotaped with a VTR camera operating at 60 fields/s for two-dimensional analysis. Coordinates of the body landmarks, racket and ball were obtained by digitizing VTR images and used to calculate kinematic variables. Results and Discussion Fig. 1 shows an example of stick pictures of the good serve and the poor serve for a female elite junior player. Some differences in both the serving motions were obtained. Ball velocities of the good serve and the poor serve were 147 km/h and 116 km/h, respectively. Impact position was lower and more forward in the poor serve than in the good serve. The forward tilt of the upper body and the flexion of the hip joint at the impact were greater in the poor serve than in the good serve. In addition, the flexion of the hip joint just before the impact and the extension of the knee joint at the beginning of the forward swing were observed in the poor serve. The difference of the impact position between the good serve and the poor serve may be caused by the motions of the trunk. We provided coaches and players with such data. Coaches and players have mentioned that these data are helpful for development of a training program for the improvement in the player`s serving motion, a detailed understanding of the player`s serving motion and so on. Therefore, these results suggest that the scientific support based on the biomechanical data would be useful for the improvement of the player`s serve technique.